2,2,3,3,4,4,4-Heptafluorobutyl Acetate: Transesterification Reaction of 2,2,3,3,4,4,4-Heptafluoro-1-Butanol and Isopropyl Acetate—Side-Product Composition - Andrei V. Polkovnichenko; Evgeniya I. Kovaleva; Nikita A. Selivanov; Tatiana D. Ksenofontova; Sergey Ya. Kvashnin; Egor V. Lupachev (Engineering Proceedings, 2024)
As the object of investigation in the present study, reactive distillation based on the transesterification of isopropyl acetate (IPAc) and 2,2,3,3,4,4,4-heptafluorobutanol (HFBol) under acidic conditions is addressed. This process aims to obtain 2,2,3,3,4,4,4-heptafluorobutyl acetate (HFBAc), which is used in the production of non-aqueous electrolytes, ethyllithium sulphate, charge retention medium, ultraviolet light-absorbing oligomers, etc. Through a combination of NMR spectroscopy and GC-MS, it was determined that during the process, the following were primarily formed in the system: target HFBAc and the by-product, isopropanol. The following side-products were identified: di-isopropyl ether, acetic acid, water, and 2,2,3,3,4,4,4-heptafluorobutyl isopropyl ether (HFB-IPEth). No bis(1H,1H-heptafluorobutyl) ether or acetic anhydride were identified in the system. For HFBol, HFBAc and HFB-IPEth the 1H, 19F and 13C{19F}), 19F-19F COSY NMR, and mass spectra were reported in this study.